Hot water immersion lowers survival, shell growth rate and lysosomal membrane stability of oysters Crassostrea virginica (Gmelin). (27th December 2013) - Mayrand, Elise; Sonier, Tina; Comeau, Luc A
Abstract This study compares the effect of two anti‐fouling treatments, hot water immersion (15 s at 60°C) and air drying (72 h) on the physiological status of the Eastern oyster Crassostrea virginica. The negative impact of hot water immersion was greater than that of air drying, but varied depending on the initial size of the oysters (40 vs. 60 mm shell height) and the time of the year (June vs. August). Groups treated with hot water exhibited a higher proportion of haemocytes with destabilized lysosomal membranes (HDLM; 47.5 ± 3.1%) than those exposed to air drying (37.5 ± 2.9%). This suggests that the oyster immunocompetency may be lowered by hot water immersion. Overall, the large oysters had lower HDLM values (32.9 ± 3.5%) than the small individuals in June (45.7 ± 2.8%) but similar values in August (46.6 ± 3.5%). Small oysters subjected to hot water immersion in June exhibited a 50% reduction in shell growth and a 50% mortality rate after one month. Our results indicate that air drying is more suitable than hot water immersion as an anti‐fouling treatment for <45 mm oysters.